193 A theoretical framework on the culture of interprofessional communication in healthcare - Clare Whitney; Shaun Besch; Heidi Preis; Xia Zheng; Elizabeth Bojsza; Susmita Pati (Journal of Clinical and Translational Science)
Objectives/Goals: The importance of interprofessional communication in healthcare is well documented. However, there has yet to be a theoretical framework for understanding this complex phenomenon. The purpose of this project was to develop a situation-specific theory about the culture of communication in the interprofessional healthcare setting. Methods/Study Population: We conducted individual virtual qualitative interviews with 16 healthcare professionals at different levels and from various disciplines. Participants were practicing clinicians at a tertiary care academic medical center. We transcribed audio-recordings of the interviews verbatim and aligned each transcript for accuracy, confidentiality, and representativeness. Data analysis was conducted using dimensional analysis, including open- and theoretical-coding utilizing an explanatory matrix for theory generation. Results/Anticipated Results: Our findings produced a situation-specific theory on the culture of interprofessional communication in the healthcare setting. Participants described the environments in which they practiced in terms of hierarchical system structures and through a conceptual perspective of resource investment. In other words, they viewed their time and their effort as valuable – and notably, scarce – resources, which they invest in patient care, interprofessional communication, and other tasks. There are two key pathways that characterize the culture of interprofessional communication: collaborative communication and transactional interactions, depending on whether an individual perceives the goals of another person, department, or level of the hierarchical institution as aligned with their own goals. Discussion/Significance of Impact: Positive cultures of interprofessional communication in the healthcare setting depend on perceived goal alignment among individuals, departments, and leadership. Future research can explore how perceptions of goal alignment are developed and empirically test this situation-specific theory in other healthcare system settings.